Industry 4.0 technologies for the adoption of the circular economy: An analysis of institutional pressures and the effects on firm performance - Jugend, Daniel [UNESP]; Fiorini, Paula De Camargo [UNESP]; Fournier, Pierre-Luc; Latan, Hengky; Chiappetta Jabbour, Charbel Jose; Scaliza, Janaina Aparecida Alves [UNESP] (Elsevier, 2024)
The present research proposes a model to investigate the influence of institutional pressures on the adoption of circular economy (CE) principles, whether Industry 4.0 technologies support this adoption, and its effect on the performance of firms. To evaluate these relationships, we collected data from 248 companies operating in Brazil. Our findings reveal the importance of external stakeholders as drivers of the transition from the linear economy to CE, highlighting the normative pressures to foster CE adoption. The study brings additional evidence in support of Industry 4.0 technologies that embrace CE implementation and shows the positive effect of their integrated adoption on firm performance. Several managerial and theoretical implications emerge from this investigation: (i) efforts to adopt both CE principles and Industry 4.0 technologies positively impact the performance of firms, and CE implementation can be facilitated when integrated with these technologies; (ii) the institutional context shaped by normative and coercive pressures can have a significant influence on CE adoption; (iii) the discussion of these novel results posits theoretical insights on CE, Industry 4.0, and their relationships with firm performance.
Keywords: Circular business; Digital technologies; Sustainability; Sustainable development